Alterations of Gut Microbiome and Serum Metabolome in Coronary Artery Disease Patients Complicated With Non-alcoholic Fatty Liver Disease Are Associated With Adverse Cardiovascular Outcomes - Hu, Xiaomin; Zhou, Ruilin; Li, Hanyu; Zhao, Xinyue; Sun, Yueshen; Fan, Yue; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2022)
Rationale: Patients suffering from coronary heart disease (CHD) complicated with nonalcoholic fatty liver disease (NAFLD) present worse cardiovascular outcomes than CHD patients without NAFLD. The progression of CHD is recently reported to be associated with gut microbiota and microbe-derived metabolites. However, it remains unclear how the complication of NAFLD will affect gut microbiota and microbe-derived metabolites in CHD patients, and whether or not this interplay is related to the worse cardiovascular outcomes in CHD-NAFLD patients. Methods: We performed 16S rRNA sequencing and serum metabolomic analysis in 27 CHD patients with NAFLD, 81 CHD patients without NAFLD, and 24 matched healthy volunteers. Predicted functional profiling was achieved using PICRUSt2. The occurrence of cardiovascular events was assessed by a follow-up study. The association of alterations in the gut microbiome and metabolome with adverse cardiovascular events and clinical indicators was revealed by Spearman correlation analysis. Results: We discovered that the complication of NAFLD was associated with worse clinical outcomes in CHD patients and critical serum metabolome shifts. We identified 25 metabolite modules that were correlated with poor clinical outcome in CHD-NAFLD patients compared with non-NAFLD patients, represented by increased cardiac-toxic metabolites including prochloraz, brofaromine, aristolochic acid, triethanolamine, and reduced potentially beneficial metabolites including estradiol, chitotriose, palmitelaidic acid, and moxisylyte. In addition, the gut microbiome of individuals with CHD-NAFLD was changed and characterized by increased abundances of Oscillibacter ruminantium and Dialister invisus, and decreased abundances of Fusicatenibacter saccharivorans, Bacteroides ovatus and Prevotella copri. PICRUSt2 further confirmed an increase of potential pathogenic bacteria in CHD-NAFLD. Moreover, we found that variations of gut microbiota were critically correlated with changed circulating metabolites and clinical outcomes, which revealed that aberrant gut microbiota in CHD-NAFLD patients may sculpt a detrimental metabolome which results in adverse cardiovascular outcomes. Conclusions: Our findings suggest that CHD patients complicated with NAFLD result in worse clinical outcomes possibly by modulating the features of the gut microbiota and circulating metabolites. We introduce “liver-gut microbiota-heart axis” as a possible mechanism underlying this interrelationship. Our study provides new insights on the contribution of gut microbiota heterogeneity to CHD-NAFLD progression and suggests novel strategies for disease therapy.